ANALISIS EFEKTIFITAS KEBIJAKAN PEMUTIHAN BEA BALIK NAMA KENDARAAN BERMOTOR DI KOTA MALANG - Husaini, Achmad (Profit: Jurnal Adminsitrasi Bisnis, 2020)
The vehicle title transfer fee (BBNKB) is a tax on the submission of the property of a vehicle as a result of two-party agreements or unilateral acts or circumstances that occur due to sale, exchange, grant, inheritance, or income into a business entity. East Java Province as one of the local governments that also collects BBNKB has its own fiscal policy to obtain optimal tax from the motor vehicle sector. The policy is the bleaching of the BBNKB and the release of administrative sanctions for the BBNKB and the Motor Vehicle Tax. So that the bleaching policy on transfer of motor vehicle fees implemented by the Malang City Samsat can be carried out, the policy must be implemented. The focus of this study is the registration mechanism, the calculation mechanism, the payment mechanism and the effectiveness ratio of the acceptance of the BBNKB bleaching policy in 2017 and 2018 in Malang. The results of the study show that the calculation mechanism for tax bleaching every year has been running according to the governor's governing procedures. It only needs to be considered by members of the council so that bleaching can be subject to multilevel tariffs, which have a death tax of more than 10 years, for example sanctions still apply. The effectiveness of this bleaching policy is the ratio of BBNKB revenue in the bleaching period. In 2017, the effectiveness ratio was 110.07%, which means it had very high effectiveness (> 100%), whereas in 2018 despite decreasing from the previous year which was 107.67%, the achievement fixed to size very effectively.